AGNs in post-mergers from the ultraviolet near infrared optical northern survey. Issue 4 (16th December 2022) - Bickley, Robert W; Ellison, Sara L; Patton, David R; Wilkinson, Scott
ABSTRACT: The kinematic disturbances associated with major galaxy mergers are known to produce gas inflows, which in turn may trigger accretion onto the supermassive black holes (SMBH) of the participant galaxies. While this effect has been studied in galaxy pairs, the frequency of active galactic nuclei (AGNs) in fully coalesced post-merger systems is poorly constrained due to the limited size or impurity of extant post-merger samples. Previously, we combined convolutional neural network (CNN) predictions with visual classifications to identify a highly pure sample of 699 post-mergers in deep r -band imaging. In the work presented here, we quantify the frequency of AGNs in this sample using three metrics: optical emission lines, mid-infrared (mid-IR) colour, and radio detection of low-excitation radio galaxies (LERGs). We also compare the frequency of AGNs in post-mergers to that in a sample of spectroscopically identified galaxy pairs. We find that AGNs identified by narrow-line optical emission and mid-IR colour have an increased incidence rate in post-mergers, with excesses of 4 over mass- and redshift-matched controls. The optical and mid-IR AGN excesses in post-mergers exceed the values found for galaxy pairs, indicating that AGN activity in mergers peaks after coalescence. Conversely, we recover no significant excess of LERGs in post-mergers or pairs. Finally, we find that the [O iii ] luminosity (a proxy for SMBH accretion rate) in post-mergers that host an optical AGN is 0.3 dex higher on average than in non-interacting galaxies with an optical AGN, suggesting that mergers generate higher accretion rates than secular triggering mechanisms.